The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0063890
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SLP-2 Was Associated with Invasion of Esophageal Squamous Cell Carcinoma

Abstract: IntroductionStomatin-like protein 2 (SLP-2), a member of the Stomatin superfamily, has been identified as an oncogenic-related protein and found to be up-regulated in multi-cancers. Nonetheless, the expression pattern and regulation of SLP-2 in human esophageal squamous cell carcinoma (ESCC) remain unexplored.MethodsImmunohistochemistry and immunofluorescence staining analysis were performed to show SLP-2 expression and location. RNAi method was used to inhibit specific protein expression. Transwell assay was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Furthermore, our data revealed expression of SLP-2 in the cytoplasm of PTC cells that was not associated with histological type, but significantly associated with tumor stage, which was confirmed by qPCR after analyzing 42 cases of PTC. The highest expression was found in stage T4 (tumor extension beyond the thyroid capsule) tumors, which is in agreement with a previous study that expression of SLP-2 is associated with invasiveness of ESCC (30). SLP-2 alterations occur early in the process of tumor formation, which may predispose to malignant transformation.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our data revealed expression of SLP-2 in the cytoplasm of PTC cells that was not associated with histological type, but significantly associated with tumor stage, which was confirmed by qPCR after analyzing 42 cases of PTC. The highest expression was found in stage T4 (tumor extension beyond the thyroid capsule) tumors, which is in agreement with a previous study that expression of SLP-2 is associated with invasiveness of ESCC (30). SLP-2 alterations occur early in the process of tumor formation, which may predispose to malignant transformation.…”
Section: Discussionsupporting
confidence: 92%
“…First, STOML2 might serve as a prognostic marker especially in human gallbladder cancer, gastric cancer, glioma, colorectal cancer, breast cancer, and pulmonary squamous cell carcinoma (19)(20)(21)(22)(23)(24). STOML2 is also involved in invasion, regulating cell growth and cell adhesion in human esophageal squamous cell carcinoma, glioma, and human endometrial adenocarcinoma (21,(25)(26)(27). In desmoid tumor that behaves aggressively by infiltrating tissues deeply, STOML2 overexpression is clinically related to PFS.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have indicated that STOML-2 was upregulated in several kinds of tumor tissue and was involved in invasion and metastasis of cancers including esophageal cancer, gastric cancer, breast cancer and glioma (19)(20)(21)(22)(23). Inhibition of STOML-2 was able to decrease cell growth and proliferation, and reduced migratory speed and invasive ability (24,25).…”
Section: Introductionmentioning
confidence: 99%